MODELING METHODS EFFECT ON STUDENT’S MOTIVATION AND LEARNING OUTCOMES IN CHEMISTRY AT MA DARUL AMININ NW AIKMUAL - Sulastri, Anis; Raehanah; Qurniati, Devi (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2023)
The purpose of this study was to determine the influence of the use of modeling methods on students' motivation and learning outcomes in Chemistry at MA Darul Aminin NW Aikmual. The sampling technique used is a nonprobability sampling technique in the form of saturated sampling. The approach used is a quantitative approach, with a quasi-experimental type and a research design that is nonequivalent control group design with a pretest-posttest type. Based on the analysis of the N-Gain motivational score, the experimental class was 24.6251 (not effective), and the control class was 14.7795 (ineffective). Then, the N-Gain score of learning outcomes in the experimental class was 63.9940 (quite effective), and in the control class it was 46.0750 (less effective). Based on the hypothesis test, it can be concluded as follows, (1) there is no effect of the modeling method on students' motivation to learn chemistry at MA Darul Aminin NW Aikmual as evidenced by a sig value of 0.117 > 0.05, (2) there is an effect of the modeling method on students' chemistry learning outcomes at MA Darul Aminin NW Aikmual is proven by a sig value of 0.000 <0.05, and (3) the influence of the modeling method on students' motivation and learning outcomes in chemistry at MA Darul Aminin NW Aikmual is proven by a sig value of 0.000 <0.05.